2019
DOI: 10.5603/fm.a2019.0015
|View full text |Cite
|
Sign up to set email alerts
|

Configuration of the circle of Willis and its two parts among Egyptian: a magnetic resonance angiographic study

Abstract: Background: We hypothesized that the collateral circulation differs in different ethnic groups. So, the aim of our work was to study variations of the circle of Willis (COW) among Egyptian and to compare our findings with the findings of other nationalities. Materials and methods: One hundred patients were studied using magnetic resonance angiography (3D-TOF-MRA). Frequency and morphologic variations in COW were studied. The diameters of the arteries of the anterior and posterior circle were verified. Finally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
(28 reference statements)
3
4
1
2
Order By: Relevance
“…A "classical" configuration with a complete entire circle and "standard" configuration of distribution and size of the arteries contributing to the CoW was found in 30.9% of cases, which is within the range of most similar studies [23,25]. The most common variation from the classical aspect was identified as the unilateral absence of one of the posterior communicating arteries (22.2%) in the posterior CoW, while in the anterior circle, the second most common configuration after the classical pattern was the unilateral absence of the precommunicating segment of an anterior cerebral artery (13.5%).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…A "classical" configuration with a complete entire circle and "standard" configuration of distribution and size of the arteries contributing to the CoW was found in 30.9% of cases, which is within the range of most similar studies [23,25]. The most common variation from the classical aspect was identified as the unilateral absence of one of the posterior communicating arteries (22.2%) in the posterior CoW, while in the anterior circle, the second most common configuration after the classical pattern was the unilateral absence of the precommunicating segment of an anterior cerebral artery (13.5%).…”
Section: Discussionsupporting
confidence: 82%
“…Out of the 20 total possible configurations of the CoW, we identified only the first 8 for the anterior, and first 6 for the posterior circle, respectively. A scarcity of these unidentified variants was cited in other similar studies with comparable study lot size [25].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A complete anterior CW was significantly higher in female than male patients (92.7% vs. 77.4%, p=0.04). The prevalence of complete anterior CW in this study was higher than an MRA-TOF study by Sherif Mohamed Zaki et al on 100 patents with no evidence of cerebrovascular disease which showed a prevalence of 66% [25]. The finding in our study was also higher than an MRA-TOF study by Shartri J et al on 513 adults without cerebrovascular disease which demonstrated a complete anterior CW in 64.3% [26].…”
Section: Discussioncontrasting
confidence: 74%
“…Anatomical variants of CoW are more common in its posterior part [34,35], some authors reporting that almost two thirds of the brain they analyzed presented anatomical variations of the posterior circulation [36]. These anatomical variants can appear either in the form of unilateral or bilateral hypoplasia/atresia of the PComAs (Figures 4-9), and as unilateral or bilateral absence of the PComAs (Figure 8) or of the PCA, or as the fetal variant of the PComA (Figures 7, 8, and 10).…”
Section: Anatomical Variants Of the Posterior Part Of The Cowmentioning
confidence: 99%